Fluctuations in House-Building and the Trade Cycle - Bowley, Marian (Review of Economic Studies, 1937)
Journal Article Fluctuations in House-building and the Trade Cycle Get access Marian Bowley Marian Bowley Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 3, June 1937, Pages 167–181, https://doi.org/10.2307/2967452 Published: 01 June 1937